Techno-Pedagogy for Promoting Problem Solving Ability and Scientific Creativity among Secondary School Students - G, Jeena K. (JOURNAL OF INDIAN EDUCATION, 2024)
Information and Communication Technology (ICT) is making a revolution in the teaching-learning process. Techno-pedagogy is the art of incorporating technology into the teaching-learning process. This study aimed to examine the effectiveness of techno-pedagogy on secondary school students’ problem solving ability and scientific creativity. The study comprised post-test non-equivalent experimental control group design using a sample of 60 students. The major findings revealed that the students, who learned through techno-pedagogy, enhanced their problem solving ability and scientific creativity. The results have great educational implications for using techno-pedagogy in teaching-learning process at the secondary level. The findings of the research motivate teachers to rethink their teaching strategies, and redefine their approaches to teaching and learning.